2009
DOI: 10.1002/app.31111
|View full text |Cite
|
Sign up to set email alerts
|

Aerocellulose based on all‐cellulose composites

Abstract: Novel aerogels (or aerocellulose) based on all-cellulose composites were prepared by partially dissolving microcrystalline cellulose (MCC) in an 8 wt % LiCl/DMAc solution. During this process, large MCC crystals and fiber fragments were progressively split into thinner crystals and cellulose fibrils. The extent of the transformation was controlled by using cellulose concentrations ranging from 5 to 20 wt % in the LiCl/DMAc solution. Cellulose gels were precipitated and then processed by freeze-drying to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…These films did not show an increase in the structure type V characteristic of several processes of starch with high amylopectin content (Raquez et al, 2008). Two overlapped weaker peaks at about 14.8 • and 16.1 • in samples added with fiber can be associated with microcrystalline cellulose (Duchemin, Staiger, & Tucker, 2010;Chang et al, 2010). Also, two overlapped peaks at 20.1 • and 22.4 • , were ascribed to cellulose II (1-10/200) and cellulose I (200) reflection (Chang et al, 2010).…”
Section: X-ray Diffraction Patternsmentioning
confidence: 84%
“…These films did not show an increase in the structure type V characteristic of several processes of starch with high amylopectin content (Raquez et al, 2008). Two overlapped weaker peaks at about 14.8 • and 16.1 • in samples added with fiber can be associated with microcrystalline cellulose (Duchemin, Staiger, & Tucker, 2010;Chang et al, 2010). Also, two overlapped peaks at 20.1 • and 22.4 • , were ascribed to cellulose II (1-10/200) and cellulose I (200) reflection (Chang et al, 2010).…”
Section: X-ray Diffraction Patternsmentioning
confidence: 84%
“…Cellulose aerogels can be fabricated from either homogeneous cellulose solutions [18][19][20][21][22][23][24][25] or heterogeneous aqueous nanocellulose suspensions. 4,7,11,13,[26][27][28][29][30][31][32][33][34] Aerogels prepared from cellulose solutions require lengthy, multiple steps of dissolving cellulose in solvents, such as alkali hydroxide/urea solution, 18 calcium thiocyanate tetrahydrate, 19 N-methyl-morpholine-N-oxide, 20,21 sodium hydroxide, 22 lithium chloride/dimethylacetamine, 23 lithium chloride/dimethyl sulfoxide 24 and ionic liquid, 25 followed by induced gelation, solvent exchange and supercritical or freeze drying.…”
Section: -17mentioning
confidence: 99%
“…Unfortunately, full dissolution irreversibly and uncontrollably denatures the original biopolymer structure and can degrade material properties (Swatloski et al 2002;Swatloski 2005;Phillips et al 2004;Haverhals et al 2009). Recently, it has been shown that composite materials may be produced by partial dissolution and reconstitution of biopolymers; a process we call ''natural fiber welding'' (Nishino et al 2003(Nishino et al , 2004Nishino and Arimoto 2005;Keckes 2005, 2007;Gindl et al 2006a, b;Nishino and Arimoto 2007;Duchemin 2008;Duchemin and Newman 2009;Duchemin et al 2007Duchemin et al , 2009Duchemin et al , 2010Soykeabkaew et al 2008Soykeabkaew et al , 2009Haverhals et al 2010a, b, c). Because biopolymers are not fully dissolved during fiber welding, material properties may be manipulated without disrupting much of their native structure.…”
Section: Introductionmentioning
confidence: 99%